Prezentacja graficzna modeli równań strukturalnych - Sagan, Adam (Graphical Visualization of Structural Equation Models, 2009)
The development of structural equation models is inherently combined with commonly accepted graphical methods of its presentation. The aim of the paper is to outline the evolution of graphical tools of SEM models visualization and the issues concerning the presentation of contemporary complex models. Additionally, the graphical tools used in popular SEM models are presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 31-41